UNROOFING AND CURRETAGE IS AN EFFECTIVE TREATMENT METHOD IN PATIENTS WITH PILONIDAL SINUS DISEASE - KAYA, DR BULENT; FERSAHOGLU, DR MAHIR; ERGIN, DR ANIL; BULUT, DR NURIYE ESEN (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Purpose:Pilonidal sinus is a chronic disease with important morbidity.There is no gold standart treatment up to date.The aim of this study is to report results of unroofing and curettage technique in pilonidal sinus surgery.Material and Methods:The data of patients who were operated with unroofing and curettage technique were collected retrospectively. Patients' age, gender, body mass index (BMI), duration of  symptoms,  presence of abscess in preoperative period, antibiotic usage and drainage, operation findings,  postoperative complications, wound healing time, recurrences were recorded. NCSS (Number Cruncher Statistical System) 2007 (Kaysville, Utah, USA) program was used for statistical analysis.Results: A total of 172 patients who underwent unroofing and curretage during  3 years period  were studied retrospectively. There were 146 (84.9%)   male and 26 (15.1%)    female patients. The mean operation time  was 18.52 ± 12.49 minutes (5-90 min).  Postoperative infection rate was 2.9% (n = 5) and bleeding rate was 1.7% (n = 3). Recurrence was found in 13 of the patients (7.6% ).  Return to work was ranged from 0 to 90 days with an average of 14.41 ± 13.10 days.Conclusion: Unroofing and curettage technique can be used under local anesthesia with outpatient basis. It  can be prefered as a first line treatment modality in pilonidal sinus surgery.